Modified sand brick with partial cement replacement using rice husk ash (RHA) - Nur Adila Binti Zainuddin (School of Environmental Engineering, University Malaysia Perlis, 2014)
The increasing demand of cement in construction industries makes many researchers find other alternatives to reduce the cost and uses of cement. The material that can be replaced by cement must a pozzolanic material as it can enhance the strength properties of concrete mixes.